Incidence of Non-Communicable Diseases & an Analysis of the General Lifestyle of Women Living in Swat Valley - Eefa, Shehzad; Haq, Ambreen; Ullah, Naeem; Ullah, Qarib (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Abstract Background: With the rise of urbanization in Pakistan, non-communicable diseases (NCDs) have been shown to have an increasing impact the healthcare system. NCDs are a leading cause of morbidity and mortality, especially in poverty stricken areas such as Swat Valley. Objective: To investigate possible lifestyle risk factors and the prevalence non-communicable diseases amongst women in Swat Valley. Materials and Methods: A community-based health survey was conducting throughout 8 villages in Swat Valley. Participants were selected using systematic sampling. Results: 600 participants were included in the study. The prevalence of hypertension, diabetes mellitus, and renal disease amongst Swat women was found to be 17.9%, 3%, and 1% respectively. Increased BMI was significantly correlated with increased incidence of hypertension (p=0.000, correlation coefficient=0.290) and diabetes mellitus (p=0.009, correlation coefficient= 0.119). Pearson correlation coefficients and two-tailed tests of significance were used for statistical analysis. Conclusion: Our study suggests the rates of NCDs amongst women in Swat are lower than the national prevalence. Nonetheless, public health educational programs and greater accessibility to health resources are needed to decrease modifiable risk factors within the community. Key words: non-communicable disease (NCDs), diabetes mellitus, hypertension, Swat Valley, women